ANALISIS GANGGUAN DAN KERUSAKAN SISTEM REM SEPEDA MOTOR SERTA PENANGANANNYA - Anitasari, Mike Elly; widiyatmoko, Widiyatmoko (Jurnal Pendidikan Vokasi Otomotif, 2024)
Brakes are one of the important components on a motorbike that supports riding comfort and safety. The aim of this research is to analyze disturbances and damage to motorbike brake systems and their handling. The research method used is direct observation of the research object, namely the brake system unit on a motorbike and literacy studies. The research was carried out from February to June. Data collection was carried out using observation techniques on brake system objects. The data obtained is then analyzed and drawn conclusions and then presented in a description of the research results. The results of the research show that disturbances and damage to the brake system include:      1) Poor brake performance and not functioning well;   2) Vibration and/or sound when braking; 3) No prisoners or failures; and 4) The brake lever or pedal does not return to normal. Handling or solutions to brake system problems and damage include light maintenance, up to replacing worn or damaged brake system components Keywords: Damage, Brake System